Atomistic simulation of primary damages in Fe, Ni and Zr - Lazarev, Nikolai P.; Bakai, Alexander S. (The Journal of supercritical fluids, 2013)
•The primary defect cluster distributions are essentially dependent on the symmetry of lattice: fcc, bcc or hcp.•Biased formation of vacancies near the voids is observed both for low energy and high energy cascades.•The defect formation in the vicinity of the helium bubbles shows the preferential formation of the self-interstitials. Prospective structural materials for supercritical water reactors have different types of crystalline lattice. Primary damage formation, energy and temperature dependencies, cluster size distributions in metals possessing fcc (Ni), bcc (Fe) and hcp (Zr) lattices are comparatively studied. While the total amounts of point defects are found to be closely approximated, the size distributions of clusters essentially depend on the lattice type. The tendency of lattices to swelling coincides with the increase of fraction of clusterized self-interstitials. Biased point defect formation near voids and bubbles in iron is revealed. It occurs that in the vicinity of these extended defects the threshold energies of the stable point defect formation are lower than those in the bulk. Collision events close to voids result in a biased formation of vacancies. Preferential formation of interstitial atoms close to helium bubbles is investigated subject to the temperature and collision cascade energy.